Fluorescence-aided molecule sorting: Analysis of structure and interactions by alternating-laser excitation of single molecules - Kapanidis, Achillefs N. (National Academy of Sciences, 2004)
We use alternating-laser excitation to achieve fluorescence-aided molecule sorting (FAMS) and enable simultaneous analysis of biomolecular structure and interactions at the level of single molecules. This was performed by labeling biomolecules with fluorophores that serve as donor–acceptor pairs for Förster resonance energy transfer, and by using alternating-laser excitation to excite directly both donors and acceptors present in single diffusing molecules. Emissions were reduced to the distance-dependent ratio E, and a distance-independent, stoichiometry-based ratio S. Histograms of E and S sorted species based on the conformation and association status of each species. S was sensitive to the stoichiometry and relative brightness of fluorophores in single molecules, observables that can monitor oligomerization and local-environment changes, respectively. FAMS permits equilibrium and kinetic analysis of macromolecule-ligand interactions; this was validated by measuring equilibrium and kinetic dissociation constants for the interaction of Escherichia coli catabolite activator protein with DNA. FAMS is a general platform for ratiometric measurements that report on structure, dynamics, stoichiometries, environment, and interactions of diffusing or immobilized molecules, thus enabling detailed mechanistic studies and ultrasensitive diagnostics.